Penerapan Metode Latis dalam Menghitung Operasi Perkalian di Kelas IV Sekolah Dasar - Rif’ah, Siti; Tiurlina, Tiurlina; Fitriasari, Novi Sofia (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The operation of multiplication counting is one of the difficult calculation operations, especially when students were working on calculating the operation of more than two or more numbers. In completing this issue, there were constraints in which because students have not memorized multiplication of 1 to 10. A technical error on working on the multiplication operation with conventional methods (stacking) students use that has been learned while sitting in grade of III. It can be done by providing new methods that can facilitate students in working with the math problem. There are many alternative methods to overcome students' difficulties. One of them is a Lattice method, a multiplication method that uses a grid to multiply two multi-digit numbers, and can reduce the level of difficulty and error. The purpose of this study was to provide an overview the influence from the use the Lattice method for calculating multiplication operations to reduce students' difficulties in solving problems. The study used a qualitative non-interactive research approach. The method used in this researcher was a literature study that collects several previous journals and researches to answer the influence of the use of the Lattice method of calculating multiplication operations against reducing students' difficulties in resolving the problems. In this study there were 14 literature studied from several journals and previous research. The results of the study there was an influence of the Lattice method of improving the learning results of mathematics, and can reduce the hardship of students in solving the trouble.